Time-varying formation control for nonholonomic wheeled mobile robots via synchronization - Sanhoury, Ibrahim M. H. (2013)
In this paper, a new synchronous control law is proposed for multiple nonholonomic wheeled mobile robots (WMR) to perform a time-varying formation task. Each robot is controlled to track its desired trajectory, while synchronized its motion with the two adjoining robots. A novel dynamic model of the WMR is derived based on Lagrange method. The Lagrange multiplier of the WMR is determined based on the input torques and the robot's velocities. The dynamic model has been divided into translational and rotational model. A synchronous translational controller is proposed to guarantee the asymptotic stability of both position and synchronization errors. A rotational controller is designed such that the robot always facing its desired position. A simulation results verified the effectiveness of the proposed synchronous controller in the formation tasks.